2012
DOI: 10.1111/j.1600-051x.2011.01840.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of parameters and methods for the professional assessment of aesthetics in dental implant research

Abstract: Objective: The purpose of the present systematic review was to evaluate the scientific literature regarding the professional assessment of aesthetics in implant dentistry. Material and Methods: An electronic search of Medline database and Cochrane Central Register of Controlled Trials was performed, and complemented by a manual search. Clinical or validation studies (Part 1) and randomized-controlled trials (RCTs) (Part 2) reporting parameters and methods for the assessment of aesthetics were included. The inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 34 publications
0
78
0
1
Order By: Relevance
“…), although as recently reported by Benic et al. , there is a strong need for a consensus on the adequate parameters to assess the aesthetics in implant dentistry. Furthermore, other clinical and radiographical outcomes were assessed together with patient‐centred outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…), although as recently reported by Benic et al. , there is a strong need for a consensus on the adequate parameters to assess the aesthetics in implant dentistry. Furthermore, other clinical and radiographical outcomes were assessed together with patient‐centred outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…Concerning patient satisfaction, it would be essential to create a white and pink esthetic index for multiunit implant reconstructions that allows the assessment of esthetic outcomes with objective parameters (Benic et al 2012). Such an "objective" analysis, correlated with the "subjective" evaluation of the patient, would help clinicians to identify parameters that make restorations more esthetically pleasing for the patient (Annibali et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…1,52,53 A recent systematic review on the assessment of periimplant esthetics concluded that because of differences between indices and study designs, comparisons between such studies should be interpreted with caution. 54 Recent research on implant esthetics typically reports their findings with the PES or White Esthetic Score/Pink Esthetic Score criteria. 14,[55][56][57] Correlations with studies using CEI criteria are therefore not fully accurate.…”
Section: Esthetic Parametersmentioning
confidence: 99%